2022
DOI: 10.3389/fcell.2021.801661
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-223-3p Protect Against Radiation-Induced Cardiac Toxicity by Alleviating Myocardial Oxidative Stress and Programmed Cell Death via Targeting the AMPK Pathway

Abstract: Objectives: Radiotherapy improves the survival rate of cancer patients, yet it also involves some inevitable complications. Radiation-induced heart disease (RIHD) is one of the most serious complications, especially the radiotherapy of thoracic tumors, which is characterized by cardiac oxidative stress disorder and programmed cell death. At present, there is no effective treatment strategy for RIHD; in addition, it cannot be reversed when it progresses. This study aims to explore the role and potential mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…TXNIP can bind and inactivate both Thioredoxin 1 (TRX1) and 2 (TRX2), which play a central role in protecting cells from oxidative stress [ 149 ]. In agreement with this protective role, Ding et al and Zhang et al reported that overexpression of this miRNA resulted in increased levels of Nrf2 by targeting kelch-like ECH-associated protein 1 (Keap1), the principal Nrf2 inhibitor [ 150 , 151 ].…”
Section: Oxidative Stress and Mirna Dysregulation In Rare Autoimmune ...mentioning
confidence: 89%
“…TXNIP can bind and inactivate both Thioredoxin 1 (TRX1) and 2 (TRX2), which play a central role in protecting cells from oxidative stress [ 149 ]. In agreement with this protective role, Ding et al and Zhang et al reported that overexpression of this miRNA resulted in increased levels of Nrf2 by targeting kelch-like ECH-associated protein 1 (Keap1), the principal Nrf2 inhibitor [ 150 , 151 ].…”
Section: Oxidative Stress and Mirna Dysregulation In Rare Autoimmune ...mentioning
confidence: 89%
“…Prior studies on radiation-induced toxicity in animal models identified several miRNAs associated with this process through experimental models. Notably, these include miR-223 ( 54 ), miR-21 ( 55 ) and miR-212 ( 56 ). Paper by Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also showed that miR-223 mimics could reduce the NLRP3 protein expression level and suppress chronic inflammation in DE ( 89 ). For radiation-induced heart disease (RIHD), miR-223 mimics could improve myocardial injury by activating adenosine monophosphate activated protein kinase (AMPK) ( 192 ). On the other hand, miR-223 inhibitors could cause hyper-activation of NLRP3 in the J774A.1 murine macrophages infected by subsp.…”
Section: The Potential Role Of Mir-223 In Clinical Treatmentmentioning
confidence: 99%